Some physical properties of sweet cherries - Polyák, N. I.; Csizmazia, Z.; Ancza, E. (International Journal of Horticultural Science, 2010)
The determination of the optimal time of the mechanical harvesting of sweet cherries has a great importance not only to prevent the fruit from mechanical injury but to find the optimal setting parameters of the harvesting machine. The primary objective of the experiments was to determine the force and work required to detach the stem from the limb and the fruit from the stem. Furthermore to measure the three main sizes (width, height, thickness) of the fruits in order to determine the sphericity, and also the pulp-stone ratio by measuring the mass of the fruit with the stone and then the mass of the stone. The average sizes of the fruits: width 19.62–27.76 mm, height 17.83–24.54 mm and thickness 17.30–23.60 mm. The stem length varied between 28.69 mm and 55.80 mm. The sphericity of each variety was above 90%. The average mass varied between 3.63 and 9.68 g. The stone mass turned to be between 0.27 g and 0.42 g. The stone-pulp ratio varied between 3.7%and 7.7%. The average pulp mass varied between 3.35 g and 9.32 g. The average values of maximum loads required to detach the sweet cherries from the stem varied between 3.23 N and, 4.12 N. The force required to detach the stem from the limb was 50–90% higher than the force needed to tear the fruit from the stem.